Identifying and addressing common undergraduate database design misconceptions - Abdelaziz, Noha; Farghally, Mohammed; Mohammed, Mostafa; Soliman, Taysir (Frontiers in Education, 2025)
Data are a crucial asset for organizations, making it essential for database designers to effectively organize and manage data using DataBase Management Systems (DBMS). DataBase design Concepts (DBCs) are central to computer and information sciences curricula, focusing on teaching students how to conceptually and logically design database systems to manage data through the DBMS. Key concepts such as conceptual data modeling and mapping models to relational schemas are fundamental to effective database design. However, students often struggle to grasp these concepts despite existing efforts to improve students' learning. Research is limited to identifying and addressing common misconceptions of students related to the DBCs. In this study, our aim is to fill in this research gap by identifying students' difficulties and challenges in comprehending DBCs, exploring their root causes, and proposing a pedagogical intervention to address these challenges early in the learning process. The primary goal is to gain a deeper understanding of how students learn and apply DBCs, formulate a clear list of students' DBC misconceptions, and finally create an online interactive visual tool aimed at addressing database design learning difficulties and misconceptions through visual presentations.